Analysis and Risk Mitigation Strategies for Occupational Accidents in Construction Activities at PT PP Site Development, Nickel Mining Area of PT X Using the HIRADC–Fuzzy TOPSIS Method - Muhammad Hafiz Aulia; Dika Rahayu Widiana; Imam Sutrisno (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
This study aims to identify potential hazards and establish priority risk control strategies in nickel mining operations using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method combined with the Fuzzy Technique for Order Preference by Similarity to Ideal Solution (Fuzzy TOPSIS) approach. The HIRADC analysis revealed several activities with high risk levels, including girder lifting, material/piping unloading, maintenance lifting, stone crushing, civil works, cathodic installation, and material loading/unloading operations. The most significant hazards identified were falling or being struck by objects, falls from heights, electrical shock, collisions with heavy equipment, and entrapment by materials. Five hazards were classified as very high risk, including falling objects (score 25), while falls from heights, electrical shock, collisions, and entrapment each scored 20. To determine mitigation priorities, the Fuzzy TOPSIS method was applied, resulting in recommended risk control strategies. The top-ranked strategies include ensuring areas are clear of falling objects and verifying lifting equipment capacity (C1), providing lifelines and full-body harnesses (C2), installing standard-compliant electrical panels with grounding (C3), segregating pedestrian pathways from heavy equipment routes (C4), and installing emergency stops and machine guards (C5). The findings demonstrate that integrating HIRADC with Fuzzy TOPSIS offers a systematic approach for effective risk management in nickel mining operations. Keywords - HIRADC, Fuzzy TOPSIS, Hazard Identification, Risk Mitigation Startegy